The Role of Turmeric Powder Supplementation in Improving Liver Performances to Support Production of Siam Catfish (Pangasianodon hypophthalmus) - Cut Dara Dewi; Damiana Rita Ekastuti; Agus Oman Sudrajat; Wasmen Manalu (Journal Omni-Akuatika, 2018)
In oviparous animals, the qualities of offspring are determined by the materials deposited in the developing oocytes that are synthesized and produced by the hepatocytes under the control of estrogen.  This study was designed to evaluate the effect of turmeric powder supplementation on liver performance to support the reproduction performances of catfish (Pangasianodon hypophthalmus). The study used 60 catfish with average body weight of ± 2 kg. The experimental catfish were assigned into a completely randomized design with 4 treatments and each treatment consisted of 15 replications. The treatment was the dose of turmeric powder supplementation in the commercial feed i.e., 0, 240, 480, and 960 mg/100 g feed.  The experimental catfish were fed two times a day in the morning and in the evening as much as 3% of body weight. The results showed that turmeric powder supplementation at a dose of 240 mg/100 g feed could inhibit liver cell destruction in the catfish as was indicated by the increase in body weight, liver weight, and DNA concentrations of liver, as well as the decrease in the liver malondialdehyde, and serum glutamic piruvic transaminase, serum glutamic oxaloacetic transaminase concentrations. Turmeric powder supplementation can be used in oviparous animals and fish to increase liver function and capacity to synthesize vitellogenin to be deposited in the developing follicles during reproduction phase.